Cyclooxygenase-2 Inhibitor: A Potential Combination Strategy With Immunotherapy in Cancer - Pu, Dan; Yin, Liyuan; Huang, Lin; Qin, Changlong; Zhou, Yuwen; Wu, Qiang; Li, Yan; Zhou, Qinghua; Li, Lu (Frontiers in Oncology, 2021)
The clinical application of immunotherapy is the milestone of cancer treatment. However, some patients have bad reaction. Cyclooxygenase-2 (COX-2) is frequently expressed in multiple cancer cells and is associated with poor prognosis. It is the key enzyme of prostaglandin E2 (PGE2) that has been proved to promote the development, proliferation and metastasis of tumor cells. Recent studies further find the PGE2 in tumor microenvironment (TME) actively triggers tumor immune evasion via many ways, leading to poor response of immunotherapy. COX-2 inhibitor is suggested to restrain the immunosuppression of PGE2 and may enhance or reverse the response of immune checkpoint inhibitors (ICIs). This review provides insight into the mechanism of COX-2/PGE2 signal in immunosuppressive TME and summarizes the clinical application and trials in cancer treatment.